Introduction to social security : policies, benefits, and poverty - Ditch, John, 1952- (London ; New York : Routledge, 1999)
An up-to-date text on an important social policy issue that needs constant updating. Essential reading for all students on social policy and administration courses.
Introduction -- 1 The nature of poverty -- 2 The aims of social security -- 3 Development of social security -- 4 Poverty and the adequacy of social security -- 5 British pensions policies -- 6 Claiming entitlements -- 7 Social security, poverty and disability -- 8 Social security and poverty -- 9 'Race', social security and poverty -- 10 Poverty and social security in the European Union.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Social security -- Great Britain; Sécurité sociale -- Grande-Bretagne.; POLITICAL SCIENCE -- Public Policy -- Social Security; Social security; Great Britain